Knowledge, beliefs, perceptions, and behavior related to the corona (COVID-19) pandemic among university students in Malawi - Stein Terje Holden; Samson Katengeza; Sarah Tione; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2022)
This study is based on a survey of 764 students at the Lilongwe University of Agriculture and Natural Resources (LUANAR), Lilongwe, Malawi. It aims to provide evidence on the extent of exposure to the pandemic among university students, their knowledge and beliefs related to the corona virus and the ways they protect themselves against getting infected, the sources of information that they rely on, and other factors influencing their knowledge, beliefs, and behavior. The study was undertaken in the period of February-March 2022 during which the fourth wave of the pandemic in the country took place and in this period the omicron variant of the virus dominated. We investigate factors associated with the extent of knowledge about the corona virus and COVID risk perceptions, information updating behavior, preferences for alternative protective measures, especially vaccination and use of facemasks. We also assessed beliefs about the effects of vaccination, trust in vaccines, and passive and active demand for vaccination. Finally, we investigate facemask use intensity and factors influencing the likelihood of infection and COVID-19 disease based on subjective self-reported experiences
Keywords: I12; I15; I18; 330; Corona; COVID-19; pandemic; university students; knowledge; beliefs; behavior